An alternative peptone preparation using Hermetia illucens (Black soldier fly) hydrolysis: process optimization and performance evaluation - Liu,Gaoqiang; Tiang,Ming Foong; Ma,Shixia; Wei,Zeyan; Liang,Xiaolin; Sajab,Mohd Shaiful; Abdul,Peer Mohamed; Zhou,Xueyan; Ma,Zhongren; Ding,Gongtao (PeerJ, 2024)
Background Hermetia illucens (HI), commonly known as the black soldier fly, has been recognized for its prowess in resource utilization and environmental protection because of its ability to transform organic waste into animal feed for livestock, poultry, and aquaculture. However, the potential of the black soldier fly’s high protein content for more than cheap feedstock is still largely unexplored. Methods This study innovatively explores the potential of H. illucens larvae (HIL) protein as a peptone substitute for microbial culture media. Four commercial proteases (alkaline protease, trypsin, trypsase, and papain) were explored to hydrolyze the defatted HIL, and the experimental conditions were optimized via response surface methodology experimental design. The hydrolysate of the defatted HIL was subsequently vacuum freeze-dried and deployed as a growth medium for three bacterial strains (Staphylococcus aureus, Bacillus subtilis, and Escherichia coli) to determine the growth kinetics between the HIL peptone and commercial peptone. Results The optimal conditions were 1.70% w/w complex enzyme (alkaline protease: trypsin at 1:1 ratio) at pH 7.0 and 54 °C for a duration of 4 h. Under these conditions, the hydrolysis of defatted HIL yielded 19.25% ±0.49%. A growth kinetic analysis showed no significant difference in growth parameters (μmax, Xmax, and λ) between the HIL peptone and commercial peptone, demonstrating that the HIL hydrolysate could serve as an effective, low-cost alternative to commercial peptone. This study introduces an innovative approach to HIL protein resource utilization, broadening its application beyond its current use in animal feed.
Keywords: Hermetia illucens larvae; Peptone; Bacterial culture; Growth kinetics